A survey of software reliability growth model selection methods for improving reliability prediction accuracy - Saidi, M. I. M. (Institute of Electrical and Electronics Engineers Inc., 2016)
Reliability is a software quality characteristic that refer to the probability a system will work correctly over a period of time. Reliability prediction is important as it can be used to plan deployment, maintenance and test activities. This study assesses the efficiency of several techniques in software reliability model (SRM) selection and aims to find out the possible enhancement to improve software reliability accuracy. The result of the survey shows most of the SRM selection technique does not optimizes the model parameter.